Creative approach to rhythmic gymnastics costume design - Shevchuk, Tetiana (Art and Design, 2025)
The present study aimed to investigate the evolution of rhythmic gymnastics costume design, in particular their aesthetic, functional and cultural components, with an emphasis on the integration of traditional national elements into the modern context. The study examined the costumes of athletes from such countries as Ukraine, China, the USA, Japan, and Uzbekistan. The materials included visual sources, technological documentation and the requirements of international regulations that define design standards, as well as scientific media publications. The study included an analysis of the historical stages of costume development, cultural symbols and innovative technologies used in their creation. The results of the study showed that the evolution of costume design reflects the complex interaction between cultural identity, technological progress and sports requirements. It was found that modern costumes strike a balance between functionality and artistic expression through the introduction of innovative materials, such as elastic mesh and thermoregulated fabrics, as well as the use of decorative elements such as rhinestones and appliqués. Ukrainian costumes demonstrated uniqueness through the integration of traditional ornaments into modern designs, while Chinese designs were marked by a harmonious colour palette that reflected cultural heritage. American costumes emphasised patriotic motifs through the use of national colours and intricate patterns. The analysis confirmed that international standards are an important factor influencing the creation of costumes, ensuring safety, comfort, and aesthetics. The conclusions of this study highlighted the importance of a harmonious combination of traditions and modern innovations in creating costumes that meet aesthetic and functional requirements. The findings open up new perspectives for research in the field of sportswear design, in particular in the context of the use of nvironmentally friendly materials and the impact on the psychological state of athletes.